Association of FAAH rs324420 (C385A) Polymorphism with High-Level Performance in Volleyball Players - Silva, Hugo-Henrique (2023)
Genetic variants are recognized to affect athletic performance, partially by modulating competition-facilitating behavior. In this study, the role of three genetic variants previously linked to athlete status was investigated among elite volleyball players. A total of 228 players (26.7 ± 8.1 years old) participating in the Portuguese championship and with multiple medalists in national and international competitions were evaluated in terms of anthropometrics, training regime, sports experience, and a history of sports lesions. SNP genotyping was conducted by means of TaqMan® Allelic Discrimination Methodology. Volleyball players showed significantly different anthropometric indicators and training habits according to sex (p < 0.05). The A allele of the genetic variant Fatty Acid Amide Hydrolase (FAAH) rs324420 (C385A) was shown to be significantly associated with superior athletic achievements under a dominant genetic model (AA/AC vs. CC, odds ratio (OR) = 1.70; 95% Cl, 0.93-3.13; p = 0.026; p < 0.001 after Bootstrap), which was corroborated by a multivariable analysis (AA/AC vs. CC adjusted OR = 2.00; 95% Cl, 1.04-3.82; p = 0.037). Age and hand length were also found to be independently associated with high-level performance (p < 0.05). Our results confirm the role of FAAH in athletic performance. More investigation into this polymorphism's potential impact on stress coping, pain, and inflammation regulation in sport, particularly in the scope of lesions prevention and treatment, is required.